Advanced methods for treating gemfibrozil and carbamazepine in wastewater: a review - Jothivel Sivanesan; Sankar Sudharsan Rameshwar; Baskaran Sivaprakash; Natarajan Rajamohan; Ahmed I. Osman; Ala’a H. Al-Muhtaseb (Environmental Chemistry Letters, 2024)
The contamination of ecosystems by pharmaceuticals and personal care products represents a significant threat to public health, necessitating innovative approaches to clean wastewater before release into aquatic environments. Here, we review the emerging strategies and methods for the remediation of gemfibrozil and carbamazepine, emphasizing toxicological impacts, advanced oxidation processes, membrane-based removal techniques, and the underlying mechanisms driving these removal processes. We found that engineered composites with strong electron transfer capabilities can enhance the removal efficiency as they boost the generation of highly oxidative radicals. For instance, a nano zero-valent ion incorporated carbon–nitrogen composite removes 100% of gemfibrozil within 60 min. Similarly, a ruthenium perovskite-based heterogeneous catalyst achieved 100% elimination of carbamazepine in 7.5 min.